DEIKSIS DALAM SYAIR MELAYU KARANGAN SYARIF ABDUL KADIR ZEIN - Amanah Hijriah (Balai Bahasa Kalimantan Barat, 2018)
For the Malays society, poetry is part of the oral tradition in the activities of custom and culture, with a person's poetry can convey messages. Syarif Abdul KadirZein is one of the poet writers in West Kalimantan, his poetry poems are poems that follow the times without leaving the characteristic of the poem itself. The purpose of this research is to describe the deixis of Malay poet by Syarif Abdul KadirZein. This research applies qualitative method, that is method which produces descriptive data descriptions written in the form of deixis in Abdul KadirZein Malay poetry. Data were collected through literature method with quotation-quoting technique. Malay poems written by Syarif Abdul KadirZein are read, then parts of poetry in each verse containing deixis form in check, marked, and recorded in the data card. Deixis contained in Abdul KadirZein's Malay poem, is personadeixis, time deixis and place deixis.